Contingent Valuation of Automated Guideway Transit in Baguio, Philippines. Issue 3 (September 2020) - Caplis, Richard Mel P.; Lopez, Dayanara S.
Highlights: Purpose: This study estimated how much are the commuters who use public and private modes of transport in Baguio City is willing to pay for the proposed Automated Guideway Transit that may be used to check its financial feasibility. Design and Methodology: Both the measure (Willingness to Pay) and the method (Contingent Valuation) employed by the study are subject to criticisms, yet the literature review shows that the measure and the method in this study are valid and reliable. Main Findings: It was found out that 77% of the respondents are willing to pay and that the computed mean WTP value is PhP 22.50 (roughly USD 0.46). Originality: This study utilized the Internet to field half of its questionnaires and the other half disseminated through face-to-face survey with randomly selected respondents. This is also the first contingent valuation study over a proposed Automated Guideway Transport system in the Philippines. Abstract: This contingent valuation study estimated the willingness to pay of the commuters for the proposed Automated Guideway Transit (AGT) in Baguio City, the Philippines. This value was used to determine the AGT's financial feasibility. This study utilized the Internet together with the use of face-to-face interviewing to elicit the responses and experiences of the commuters. Both the measure (Willingness to Pay) and the method (Contingent Valuation) employed in the study are subject to criticisms, yet the literature review shows that the measure and the method in this study are valid and reliable. It was found out that 77% of the respondents are willing to pay and that the computed mean WTP value is PhP 22.50 (roughly USD 0.45).